Characterization of the clinic and therapy in patients with ear, nose and orofarynge abscess diagnose admitted in the hospital Central Universitario Dr. "Antonio María Pineda" (Boletin Médico de Postgrado, 2018)
Deep head and neck infections are public health very complex problem to developing countries. The early diagnose and treatment is very important, since structures and vital organ dissemination may develop heavy problems even death. By means of characterize the clinic and therapy of the patients with ear, nose and orofarynge abscess diagnose admitted in the Hospital Central Universitario Dr. "Antonio María Pineda", a descriptive and retrospective study was realized, by reviewing the clinical stories of the patients with the mentioned diagnose admitted in the Hospital during the 2012-2014 period. A sample of 32 patients were obtained with an age average of 31.28 ± 12.24 years old (age ranged from 16 to 71 years old), 17 female (53.13%). The more frequent anatomic localization was the peritonsillar abscess with a 62.16%, followed by the submandibular and parotid abscess with an 8.11%. The more frequent clinical characteristic were the odynophagia 75.00%, trism 68.75% and fever 65.23%. The Sulbactan-Clindamicine Ampicillin combination was the most used with a 59.38%. 56% of the times Dexametasone was used. 62.5% of the patients needed surgical drain. The time for hospital stay most commons was 3 to 7 days with a 59.38%.In conclusion, know the characteristics of different abscesses in the field of Otolaryngology allows us to make an early diagnosis and indicate appropriate medical and / or surgical treatment to avoid possible complications. KEY WORDS: Abscess. Nose. Ear. Orofarynge. Adults.
Keywords: Abscess; Nose; Ear; Orofarynge; Adults